CORRELATIONS BETWEEN CARIOUS DISEASE AND INFLAMMATORY SYNDROME IN RHEUMATOID ARTHRITIS - CRISTINA-ANGELA GHIORGHE; CRISTINA IORDACHE; RODICA CHIRIEAC; AIDA CORINA BADESCU; CODRINA ANCUTA (Romanian Society of Oral Rehabilitation, 2018)
We aimed to analyse parameters defining carious disease in patients with rheumatoid arthritis (RA) and to evaluate potential correlations with inflammatory systemic parameters related to RA. Materials and method. We performed a complex clinical oral exam (DMFT, PI, RFR, RFS, CT) and inflammatory tests (ESR, C-reactive protein) and ASLO in seven patients known with RA. The results were statistically analyzed by SPSS 16 programs and Spearman`s correlation. The results showed a positive correlation between ASLO and DMFT, PI, CT, ESR and DMFT, PI, CT, C-reactive protein and variable: CT, PI; negative correlations were reported between ASLO and RFR, RFS, while C-reactive protein also associated with DMFT, RFR, RFS. Conclusions RA can influence the patient's cariogenic risk.